Echinoderms communities in the Tunantal area, Gulf of Cariaco, Venezuela. - Gómez-Maduro, María Cecilia (2015)
Echinoderms are relevant in the structure of marine benthic assemblages, both due their diversity and their ecological niche. However, studies related with occurrence, abundance and patterns of distribution of echinoderms in Venezuela are still scarce. In the present study we describe the echinoderms in shallow-waters habitats (corals patches, Thalassia beds, sandy bottom, rocky subtidal shore, and mouth of river) at Tunantal bay, Golfo de Cariaco, Venezuela, an area that face threats related with the increase of urban development. Samples were performed during September - October 2010 and February - April 2011, using quantitative (1 m2 plots) and qualitative diving observations. Measurements include density, number of species, evenness, Shannon diversity and similarities between habitats based on Bray-Curtis and Sorensen Indexes. Differences in the structure of echinoderm assemblages were detected between habitats. The overall number of echinoderm species in the area was estimated in 40 ± 3.02. Coral patches and rocky shores showed more species and abundance, evenness and Shannon diversity than others habitats. Although the former habitats are similar in evenness and Shannon diversity, differences in the structure of the assemblages were detected. In coral habitats Echinometra viridis, Ophiactis savignyi and Ophiothrix angulata were the dominants species of the assemblages, meanwhile in rocky shores E. lucunter and Ophiocoma echinata were dominants in abundance followed by Ophionereis reticulata. Other habitats of the bay (Thalassia beds, sandy bottom and mouth of river) showed very low diversity and abundance of echinoderms, in some cases only occasional occurrence. Substrate heterogeneity is proposed as the main driving factor of the diversity and structure of the echinoderms assemblages in the bay. Moreover coral patches and rocky shores offer a substratum to dominant species (E. viridis, E. lucunter and O. echinata), but habitat differences in terms of substratum, depth and wave stress could explain the differences in the echinoderm assemblage. The overall echinoderm diversity is promoted by the differences of habitats in the bay and the changes of species composition between habitats.